The bird and bat species in the vicinity of Lake Mainit, Mindanao - Garingarao, Carlo Jan P.; Mata, Emmylou V.; Nuñeza, Olga M. (2003)
The birds and volant mammals present in the vicinity of Lake Mainit, Mindanao were assessed. Two sampling sites were chosen ; Site 1 at one of the lowland hills surrounding the lake (250-525 masl) and site 2 at an agricultural area at the lake's edge (10-20 masl). Specimen collection was performed through mist-netting for both birds and volant mammals; complemented by bamboo snap traps and birdwatching for birds. Thirty-seven bird species and six bat species were recorded from the two sampling sites, with and endemicity of 21.62% and 33.33%, respectively. Overall species diversity indices (Shannon-Weaver) were calculated at 3.30 and 0.76, respectively. None of the recorded species was considered to be endangered or threatened. Observed threats to the area's biodiversity included ongoing illegal logging and clearing for plantations and farming, quarrying at the lake's edge, bird trade, bat hunting, increase in water pollution due to domestic wastes, and the proposed construction of a hydroelectric plant. Results imply that there is a need to conserve existing endemic species in the area, aid the highly disturbed ecosystems recover, and maintain the lake's water quality.
Keywords: Birds; Bats